Overview of the Production Process Layout Through the Technology Group at PT. Kayu Mebel Indonesia, Semarang - Antonius Cahyono; Rusdiyantoro Rusdiyantoro; M. Nusron Ali (Asian Journal of Social and Humanities, 2023)
This research was carried out at PT. Kayu Mebel Indonesia, Semarang. The company in this wood processing area has a production form that is elongated to the factory shape so that production is less than optimal. So it is necessary to revise the production layout by applying the Rank Order Cluster Algorithm (ROCA) and Similarity Coefficient (SC) methods, both of which are used to obtain a factory layout scheme that produces maximum production in order to achieve minimum back trafficking values. In order to know the forward and backward scores obtained through analysis from to chart. The results of the study obtained forward results which were originally 70.4% to 83.1% or an increase in the forward value of 12.7% from the initial layout. As for the backtracking value which was originally 29.6% to 16.9% or a decrease in the backtracking value of 12.7% from the initial layout. The results of the initial spacing of 1562.83 meters became 1466.37 meters or experienced a 7% savings from the previous layout. As for material handling costs, which were originally Rp. 760,280, - to Rp. 690,314, - or experienced a 7% savings from the previous layout